Detailed compositional characterization of plastic waste pyrolysis oil by comprehensive two-dimensional gas-chromatography coupled to multiple detectors - Toraman, Hilal E.; Dijkmans, Thomas; Djokic, Marko R.; Van Geem, Kevin M.; Marin, Guy B. (Journal of Chromatography A, 2014)
•Combination of the information of an FID, SCD, NCD and TOF-MS on a GC×GC.•Quantitative and qualitative characterization of plastic waste pyrolysis oil.•Trace impurity measurement of sulfur and nitrogen compounds in a complex matrix. The detailed compositional characterization of plastic waste pyrolysis oil was performed with comprehensive two-dimensional GC (GC×GC) coupled to four different detectors: a flame ionization detector (FID), a sulfur chemiluminescence detector (SCD), a nitrogen chemiluminescence detector (NCD) and a time of flight mass spectrometer (TOF-MS). The performances of different column combinations were assessed in normal i.e. apolar/mid-polar and reversed configurations for the GC×GC–NCD and GC×GC–SCD analyses. The information obtained from the four detectors and the use of internal standards, i.e. 3-chlorothiophene for the FID and the SCD and 2-chloropyridine for the NCD analysis, enabled the identification and quantification of the pyrolysis oil in terms of both group type and carbon number: hydrocarbon groups (n-paraffins, iso-paraffins, olefins and naphthenes, monoaromatics, naphthenoaromatics, diaromatics, naphthenodiaromatics, triaromatics, naphthenotriaromatics and tetra-aromatics), nitrogen (nitriles, pyridines, quinolines, indole, caprolactam, etc.), sulfur (thiols/sulfides, thiophenes/disulfides, benzothiophenes, dibenzothiophenes, etc.) and oxygen containing compounds (ketones, phenols, aldehydes, ethers, etc.). Quantification of trace impurities is illustrated for indole and caprolactam. The analyzed pyrolysis oil included a significant amount of nitrogen containing compounds (6.4wt%) and to a lesser extent sulfur containing compounds (0.6wt%). These nitrogen and sulfur containing compounds described approximately 80% of the total peak volume for respectively the NCD and SCD analysis. TOF-MS indicated the presence of the oxygen containing compounds. However only a part of the oxygen containing compounds (2.5wt%) was identified because of their low concentrations and possible overlap with the complex hydrocarbon matrix as no selective detector or preparative separation for oxygen compounds was used.